Crime in Ukraine in Conditions of Martial Law - Bohatyrova, Olha; Yurchyshyn, Vasyl; Buriak, Kateryna; Mykhalik, Oleksandr; Marchuk, Valerii (Jurnal Cita Hukum, 2023)
The article examines criminality in Ukraine in conditions of martial law. It has been proven that crime is a social phenomenon that cannot exist outside the social environment because it manifests itself in crimes and criminal misdemeanors of a certain part of society’s members. Substantiated is opinion that crime with its ideology, dynamics, and geography causes globalization processes that change, improve or worsen people’s lives, their rights and freedoms, which are undoubtedly related to many objective and subjective factors of society development. An analysis of modern concepts presented in works of domestic scientists has been carried out. The author’s definition of crime in conditions of martial law has been formulated and its main features has been revealedKeywords: Administrative-Legal Aspect, Environmental Aspect, Decentralization, Customs Aspect, Public Authority, Local Self-Government, Social Aspect.